2017
DOI: 10.1364/oe.25.031394
|View full text |Cite
|
Sign up to set email alerts
|

Micro-displacement reconstruction using a laser self-mixing grating interferometer with multiple-diffraction

Abstract: In this paper, we demonstrated an improved laser self-mixing grating interferometer (SMGI) with autocollimation design which can avoid the disturbance from the light feedback of the zero-order diffraction beam. In order to obtain higher optical subdivision, SMGI with multiple-diffraction is implemented. Both theoretical analysis and experimental work show that the proposed system for displacement measurement can achieve high sensitivity and low measurement uncertainty. Using the proposed system, different form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 18 publications
(18 reference statements)
0
12
0
1
Order By: Relevance
“…Additionally, the maximum peak-peak value of the external cavity mode oscillation is about 0.056 as shown in (c), whereas the maximum peak-peak value of the relaxation oscillation is about 3.179 as shown in (a), more than 50 times larger than the external cavity mode oscillation. Figure 4(d) is the filtered SMI signal with a low-pass filter with cut-off frequency of 10 MHz, it can be seen from which the relaxation oscillation and external cavity mode oscillation are filtered, showing a conventional SMI as in the literature [5][6][7]. From above analysis, it can be concluded that there are two kinds of high-frequency oscillations in the SMI signals when the SMLD in moderate feedback regime with undamped RO.…”
Section: Simulation and Analysismentioning
confidence: 69%
See 1 more Smart Citation
“…Additionally, the maximum peak-peak value of the external cavity mode oscillation is about 0.056 as shown in (c), whereas the maximum peak-peak value of the relaxation oscillation is about 3.179 as shown in (a), more than 50 times larger than the external cavity mode oscillation. Figure 4(d) is the filtered SMI signal with a low-pass filter with cut-off frequency of 10 MHz, it can be seen from which the relaxation oscillation and external cavity mode oscillation are filtered, showing a conventional SMI as in the literature [5][6][7]. From above analysis, it can be concluded that there are two kinds of high-frequency oscillations in the SMI signals when the SMLD in moderate feedback regime with undamped RO.…”
Section: Simulation and Analysismentioning
confidence: 69%
“…As a minimum part-count scheme, various SMI-based applications have been developed in the industrial and laboratory environment, such as measurement of displacement, velocity, vibration, alpha factor, refraction index, strain, acoustic emission, etc. [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Self-mixing interference occurs when a portion of light emitted from a laser source is reflected or scattered back into the laser cavity by a remote target, the reflected light mixes with the light inside the cavity, causing a modulation of both the amplitude and the frequency of the lasing field. Using a simple opto-electronic system, SMI-based sensors have been developed for various applications of displacement, 5 7 distance, 8 10 flow, 11 15 imaging, 16 , 17 etc. Recently, the rapid development of semiconductors, advanced manufacturing has given rise to a growing demand for multiplexed displacement sensors.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is difficult to regulate the tilt angle of the target to obtain MSMI in practice. In 2017, Guo et al [18] proposed an improved laser self-mixing grating interferometer (SMGI) and introduced an electro-optic modulator (EOM) for phase modulation, thus achieving nanoscale micro-displacement reconstruction. However, due to the limitation of diffraction efficiency, it is impossible to achieve a higher number of diffraction times.…”
Section: Introductionmentioning
confidence: 99%